السمات القيادية المفضلة من وجهة نظر الإداريين في المنظمات السياحية في مدينة طرطوس دراسة استكشافية على المنظمات السياحية في مدينة طرطوس - ديوب, محمد عباس; كنعان, سلسل (Latakia University Journal - Economic and Legal Sciences Series, 2016)
تلعب القيادة دوراً محورياً في أي منظمة، فعليها يتوقف نجاح وفشل كافة الموارد المتواجدة في المنظمة مهما بلغت كفاءتها، أي هي نقطة البداية والنهاية في أي منظمة مهما اختلف شكلها، لذلك كان لابد من التركيز على الدراسات التي تتناول موضوع القيادة، والسمات القيادية التي يجب أن يتمتع بها القائد حتى يكون أكثر فاعلية. هدف البحث الى التعرف على السمات القيادية المفضلة لدى الإداريين في المنظمات السياحية. ومن أجل بلوغ هذا الهدف تم توزيع الاستبيان الذي يتضمن 39 سمة من السمات القيادية على 82 اداري في المنظمات السياحية في محافظة طرطوس، وتم التحليل باستخدام برنامج spss وتم ترتيب السمات من الأكثر تفضيلاً الى أقلها تفضيلاً، وكانت النتائج كما يلي: المجموعة الاولى تتضمن أول عشر سمات الأكثر تفضيلاً مرتبة أيضا بحسب تفضيلها من الأعلى الى الأدنى كالتالي: تحمل المسؤولية والخبرة، العدل، حل المشكلات، الكفاءة، الجرأة في اتخاذ القرار، القدوة الحسنة، ادارة الوقت، قوة الشخصية، الاهتمام بالتدريب، التوجيه. المجموعة الثانية: الحيوية والنشاط-وضوح الاسلوب-الامانة والصدق-الاقناع-حسن المظهر-احترام الآخرين-التخطيط-تشجيع العمل كفريق-الثقة بالنفس-الاخلاص-الحماس-الشجاعة -الحكمة -الاطلاع والمعرفة-تبادل الآراء. المجموعة الثالثة: الاستقلالية-التغيير والتطوير-الصبر-الذكاء-العطاء والطموح-الهدوء-تفويض الصلاحيات-المرونة-الانتماء-الرقابة والمتابعة-الحزم-التواضع-العلاقات الانسانية. The leadership plays pivotal role in any organization, where the success and the failure of all resources in organization depends upon. It is the starting point and the end of any organization, whatever its shape. Therefore, it was necessary to focus the studies in the subject of leadership, and leadership traits that should be characterized by it In order to be more effective. Therefore, the goal of this study is to recognize on the preferred leadership traits for Administrators in tourist organization. The questionnaire, which includes 39 traits of leadership, was distributed on 82-administration leader in tourist organizations in Tartous. The analysis has been using the spss program. We arrange the traits from the most preferred to the least preferred, and the results were as follows: The first group includes the first ten traits most favored and its arranged according to their preference from the top to the lowest as follows: take responsibility and experience, Justice, problem solving, efficiency, boldness in decision-making, setting a good example, time management, strength of character, attention to training, guidance. The second group-Vitality activity- Clear style- Honest-Persuasiveness –Good appearance-Respect for others-Planning-Encourage teamwork -Self, Confident –Faithfulness-Enthusiasm-Courageous-Wisdom-Knowledgeable-Exchange views. The third group Independence-change and development- patience- intelligence -the ambition-quiet-devolution of powers-flexibility-affiliation-control and monitoring-beams-humility-human relationships.